Enhancing Procedural Understanding of Group Counseling Practices Through Video-Based Learning: An Experimental Study With Counseling Students - Suryani, Rina; Pristanti, Nindya Ayu; Marito, Yeni (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2024)
Developing procedural understanding of group counseling practices is a critical objective in counselor education, as effective counseling requires not only conceptual knowledge but also the ability to implement counseling procedures accurately and systematically. However, many counseling students experience difficulties translating theoretical knowledge into procedural practice. This study aimed to examine the effectiveness of video-based learning in enhancing counseling students’ procedural understanding of group counseling practices. Using a quantitative experimental approach with a one-group pretest–posttest design, the study involved 36 undergraduate counseling students enrolled in a guidance and counseling program at a public university. Students’ procedural understanding was measured before and after the implementation of a video-based learning intervention that demonstrated the stages and procedures of group counseling. Descriptive analyses indicated substantial increases in mean scores and positive shifts in procedural understanding categories following the intervention. Inferential analysis using the Wilcoxon Signed-Rank Test revealed a statistically significant difference between pretest and posttest scores (Z = −3.48, p < .001). The findings indicate that video-based learning effectively enhances counseling students’ procedural understanding of group counseling practices. This study contributes to the counselor education literature by providing empirical evidence supporting video-based learning as a pedagogical strategy for teaching procedural aspects of group counseling and highlights its potential to bridge the gap between theory and practice in counselor training.